ANTIBACTERIAL ACTIVITY OF EXTRACTS OF THREE CROTON SPECIES COLLECTED IN MPUMALANGA REGION IN SOUTH AFRICA - Selowa, Sefudi Christina; Shai, Leshweni Jeremia; Masoko, Peter; Mokgotho, Matlou Phineas; Magano, Solomon (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The antibacterial activities of three Croton species were compared using bioautography and the serial microdilution methods. The methanolic extracts of all the species had low activity against Escherichia coli. The highest activity was observed with Croton megalobotrys against Enterococcus faecalis with a minimal inhibitory concentration (MIC) value of 0.02 mg/ml. Croton steenkapianus extracts were the least active of the species investigated, only managing an MIC value of 0.625 mg/ml against Pseudomonas aeruginosa. Croton megalobotrys leaf powder was serially extracted using solvents of various polarities. The lowest MIC value (0.06 mg/ml) of the serially extracted fractions was observed with acetone against Pseudomonas aeruginosa. The liquid-liquid fractions of the methanol extract of Croton megalobotrys were also tested. The lowest MIC value of 0.02 mg/ml was observed with n-hexane fraction against Enterococcus faecalis. The carbon tetrachloride fraction was further fractionated using column chromatography with silica as the immobile phase. The resulting seven fractions were tested for activity following the bioassay-guided practice, and it emerged that the first three fractions had active compounds against Staphylococcus aureus when the bioautography method was used.